1996
DOI: 10.1046/j.1526-4610.1996.3603154.x
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Magnesium Sulfate Rapidly Alleviates Headaches of Various Types

Abstract: Intravenous infusion of 1 gram of MgSO4 results in rapid relief of headache pain in patients with low serum IMg2+ levels. Measurement of serum IMg2+ levels may have a practical application in many types of headache patients. Low serum and brain tissue ionized magnesium levels may precipitate headache symptoms in susceptible patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(88 citation statements)
references
References 35 publications
2
83
3
Order By: Relevance
“…However, according to the observation on the limited number of patients, recurrent headaches occurred earlier with magnesium than with sumatriptan treatment. Our results are in accordance with those of Mauskop et al [12,13], who reported successful headache relief with the intravenous magnesium treatment in 80% of patients with various types of headache. In the first of two double-blind, randomized studies of intravenous magnesium treatment, comparison of the efficacies of prochlorperazine and magnesium sulfate revealed a moderate magnesium efficacy (56%) in acute headache treatment [14].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, according to the observation on the limited number of patients, recurrent headaches occurred earlier with magnesium than with sumatriptan treatment. Our results are in accordance with those of Mauskop et al [12,13], who reported successful headache relief with the intravenous magnesium treatment in 80% of patients with various types of headache. In the first of two double-blind, randomized studies of intravenous magnesium treatment, comparison of the efficacies of prochlorperazine and magnesium sulfate revealed a moderate magnesium efficacy (56%) in acute headache treatment [14].…”
Section: Discussionsupporting
confidence: 93%
“…Several trials of intravenously administered magnesium in the treatment of headache attacks (including migraine) were conducted with a wide spectrum of results, ranging from very enthusiastic [12][13][14] to highly disappointing [15]. Therefore, the aim of this open study was to estimate the efficacy of intravenous magnesium sulfate (1 g) in the treatment of severe migraine attacks.…”
Section: Introductionmentioning
confidence: 99%
“…Mauskop and Altura found significant rise of the ratio during the luteal phase when progesterone levels peaked and predicted its possible role in menstrual migraines. 17,18 The Serum Ca 2+ /Mg 2+ ratio in menopause was significantly lower than that in ovulatory and luteal phases of normal cycling women in the present study. No significant positive correlation was obtained between estrogen and progesterone with Ca 2+ /Mg 2+ ratio in menopausal women (Table 1-4).…”
Section: Discussioncontrasting
confidence: 56%
“…This number is somewhat higher than in the studies of Pfaffenrath et al [20] (28.6%) and of Peikert et al [21] (18.6%), but in the latter study 2 patients (5%) had to discontinue treatment because of diarrhea [21]. This side effect seems to occur only with oral intake of magnesium, as we did not encounter any gastrointestinal side effects in our study with intravenous MgSO 4 [43], nor did Mauskop et al in a similar study [44]. Our total frequency of side effects with magnesium (47.8%) is comparable to that in other studies which reported frequencies of 37.2% [21] and 45.7% [20].…”
Section: Discussioncontrasting
confidence: 49%